Escenario de la guerra de Independencia - Eduardo Flores Clair (Nuevo mundo - Mundos Nuevos, 2009)
Presentation of events New Spain’s’ war of Independence in the Veracruz region. Examination of the role played by military corpses concerning their composition as well as their effective participation in different battles. Outlining of the contribution of “jarochas” militia in the success of the insurgents and the participation of several actors in Independent México’s policy.